PERAN GURU DALAM MENGATASI KESULITAN BELAJAR SISWA PADA MATA PELAJARAN AL QUR’AN HADIS KELAS X DI MA AL- ITTIHAD BELUNG PONCOKUSUMO MALANG - Winda Ambarwati; Mohammad Afifulloh; Dwi Fitri Wiyono (VICRATINA, 2022)
Difficulties in the subjects of Al Qur’an Hadidt Class X at MA Al-Ittihad Belung Poncokusumo Malang” the focus of this research is how is the role of a teacher to overcome the learning difficulties of class X students at MA Al-Ittihad? what are the supporting and the inhibiting factors to overcome the learning difficulties of class X MA Al-Ittihad Belung Poncokusumo Malang? and what is the solution to overcome the learning difficulties of class X students at MA Al-Ittihad?  This research is a case study researchwith a place in MA Al- Ittihad Belung Poncokusumo Malang. Data collection uses interviews, observation adan dokumentation methods, data analysis is carried out by taking important data and after that making conclusions. and to test the validity of the data to test validity of the data carried out by extending the observations, increasing, persistence, triangulation, peer discussion, member check. based on the results of research that has been obtained regarding the role of teachers in overcoming student learning difficulties in the subjects of Al Qur’an Hadidt at MA Al-Ittihad Belung Poncokusumo Malang, namely the role of teachers to overcome learing difficulties for students by approaching students, to identify learning difficulties for students by approaching students, to identify difficulties towards students, provide direct guidance or direction, familiarize students to always read the Al Qur’an at home.